Preparing Graduate Students to Teach Math: Engaging with Activities and Viewing Teaching Models - Maria Boeke Mongillo (Networks: An Online Journal for Teacher Research, 2016)
Teacher self-efficacy is the belief a teacher holds that he or she can make a difference in student achievement, even when the student is difficult or unmotivated (Guskey & Passaro, 1994). It has been linked to positive teacher practices and student outcomes. This mixed methods study of preservice elementary and early childhood math teachers explored how having students engage in hands-on activities and view video teaching models in a graduate mathematics methods course influenced their teacher selfefficacy for math. The study took place in two phases, with course modifications made between the two. Statistical analyses of pre- and post-test scores on the Mathematics Teaching Efficacy Beliefs Instrument showed positive outcomes in Phase 1 but not Phase 2. Qualitative data in both phases suggested working with hands-on materials and viewing video models was beneficial to building student self-efficacy and in improving mathematical content knowledge.